TIPOLOGI KEPEMIMPINAN ABU BAKAR ASH – SHIDDIQ TERHADAP NILAI –NILAI PENDIDIKAN AGAMA ISLAM : (Abu Bakar Ash – Shiddiq's Leadership Typology On The Values Of Islamic Religious Education) - Moh Safik Al Mubarok; Arief Rahman Muhammad (Raqib: Jurnal Studi Islam, 2024)
Leadership is a matter of relationships and influence between the leader and those he leads. Leadership emerges and develops as a result of automatic interaction between the leader and the individuals being led. The aim of this research is to find out what the leadership of Abu Bakar Ash - Shiddiq was like and the values ​​of Islamic religious education contained in his leadership. Abu Bakar Ash - Shiddiq was the first Caliph in the Khulafa al - Rasyidin and this was a gift and privilege given to him by Allah SWT, which was based on very strong faith, he had done a lot. He was always ready to defend the Prophet on his missionary journey. As his defense of the Muslims. The interests of Rasulallah SAW took precedence over the interests of his own personality. Even in all situations, he always accompanied the Prophet SAW struggle. The perfection of his morals provides values ​​of Islamic religious education that we should emulate, including; Assertiveness, courage, generosity, justice, honesty and authority.